A subcriação e a História-Mãe em J.R.R. Tolkien - Albuquerque, Rebeca Emanuele Arruda de Sousa (2025)
This paper aims to define, investigate, and understand how the Author's Mother History by J.R.R. Tolkien influenced all areas of his existence, including the artistic production of his fictional stories. Seeking to link Tolkien's Legendarium to the Christian roots of his Catholic faith, the research gathers numerous points that aim to demonstrate how the narrative scope of his fictional work is the greatest witness to his devotion to the Christian religion. Through a bibliographic research method, this text brings together a significant number of authors, articles, and experts who attest to the relevance of Catholicism in the life and work of the creator of Middle-earth, challenging those who claim his mythological invention is opposed to Christianity in general. Throughout his fantastic narratives, Tolkien's faith is revealed through symbols present in the plot, as well as an emphasis on what is virtuous, true, and beautiful through clear distinctions between the morality of the characters. Through scenes where evil battles good or where virtue confronts vice, there lies a Christian mark. By including his beliefs through the logic of Subcreation, Tolkien positioned himself as a true subcreator when he made Christianity a subtle guest in certain parts of his works—soft enough to be overlooked by some, but present enough to capture the attention of others. It is concluded that his works reflect the exact synthesis of Subcreation, as the stories subtly echo like a refracted light derived from the original hue, just as written in his poem "Mythopoeia."